Synchronous papillary endometrial and ovarian cancer in a 64-year-old woman - Bharaswadkar, Ganesh B.; Babacan, Nalan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Obesity, nulliparity, and comparatively younger age may attribute a “hormonal field effect” which leads to the development of synchronous endometrioid cancers. The morphological unit consisting of the uterus, fallopian tubes, and ovary as part of the Mullerian system may explain the synchronous appearance of these malignancies. Synchronous endometrial and ovarian cancer (SEOC) is defined as the simultaneous presence of these dual cancers at the time of diagnosis as opposed to metachronous cancer where these two cancers are diagnosed at different chronologic time points. Synchronous malignancies in the female genital tract are very rare entities. Synchronous endometrial and ovarian tumors must be differentiated from either primary endometrium or ovarian tumors with metastasis. The landmark criteria for diagnosing such cases have been laid down by Ulbright and Roth.